Implementasi Media Pembelajaran Gamifikasi Quizizz Pada Materi Pendidikan Agama Islam Dalam Meningkatkan Motivasi Dan Interaksi Siswa SMK Ar-Roudhoh Beji Pasuruan - Mohamad Diyan Romadoni; Achmat Mubarok; Muhammad Nur Hadi; M. Jamhuri (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
Lack of teacher attention in implementing interesting learning methods can make students less enthusiastic about learning in class, especially in Islamic Religious Education subjects at Ar-Roudhoh Beji Pasuruan Vocational School. So it can also cause the learning atmosphere in the classroom to be less interactive and can cause students to lack the skills to think critically when learning in class. In this case, gamification plays a very important role in the development of Islamic Religious Education teaching materials. Therefore, the author wants to know more about the implementation of Quizizz Gamification Learning Media in Islamic Religious Education Materials in Increasing Student Motivation and Interaction (Case Study at Ar-Roudhoh Beji Pasuruan Vocational School). The aim of this research is to describe the implementation of Quizizz Gamification Learning Media in Islamic Religious Education Materials in Increasing Student Motivation and Interaction (Case Study at Ar-Roudhoh Beji Pasuruan Vocational School). The type of research used is qualitative descriptive research. Where the data obtained in this research is in the form of stories or processes in the use of techniques used in data collection in the form of observation, interviews and documentation. The results of implementing Quizizz Gamification Learning Media in Islamic Religious Education Materials are to foster a high sense of enthusiasm for learning so that the use of Quizizz gamification in Islamic Religious Education learning can increase student motivation and interaction at Ar-Roudhoh Beji Pasuruan Vocational School. Abstrak Kurangnya perhatian guru dalam menerapkan metode pembelajaran yang menarik dapat membuat siswa kurang bersemangat dalam mengikuti pembelajaran di kelas, khususnya pada mata pelajaran Pendidikan Agama Islam di SMK Ar-Roudhoh Beji Pasuruan. Sehingga hal tersebut juga dapat menyebabkan suasana pembelajaran di kelas menjadi kurang interaktif dan dapat menyebabkan siswa kurang memiliki keterampilan berpikir kritis saat belajar di kelas. Dalam hal ini, gamifikasi memegang peranan yang sangat penting dalam pengembangan bahan ajar Pendidikan Agama Islam. Oleh karena itu, penulis ingin mengetahui lebih jauh tentang Implementasi Media Pembelajaran Quizizz Gamification pada Materi Pendidikan Agama Islam dalam Meningkatkan Motivasi dan Interaksi Siswa (Studi Kasus di SMK Ar-Roudhoh Beji Pasuruan). Tujuan dari penelitian ini adalah untuk mendeskripsikan Implementasi Media Pembelajaran Quizizz Gamification pada Materi Pendidikan Agama Islam dalam Meningkatkan Motivasi dan Interaksi Siswa (Studi Kasus di SMK Ar-Roudhoh Beji Pasuruan). Jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif. Dimana data yang diperoleh dalam penelitian ini berupa cerita atau proses dalam penggunaan teknik yang digunakan dalam pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil penerapan Media Pembelajaran Gamifikasi Quizizz pada Materi Pendidikan Agama Islam adalah menumbuhkan rasa semangat belajar yang tinggi sehingga penggunaan gamifikasi Quizizz dalam pembelajaran Pendidikan Agama Islam dapat meningkatkan motivasi dan interaksi siswa di SMK Ar-Roudhoh Beji Pasuruan.